SYSTEMATIC LITERATURE REVIEW: ANALISIS SELF-CONFIDENCE DALAM COGNITIVE LOAD PADA PEMBELAJARAN MATEMATIKA - Claudia Salsabila; Etika Khaerunnisa; Indiana Marethi (ALGORITMA: Journal of Mathematics Education, 2026)
Abstract Mathematics learning requires integrating affective and cognitive aspects, especially when students face complex tasks. This study aims to analyze the role of Self-confidence in Cognitive load in mathematics learning through a Systematic Literature Review. The review followed the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. Data were collected from Google Scholar using the Publish or Perish 8 application. From 100 initial articles, 17 relevant articles were selected for analysis. The findings show that studies on Self-confidence mainly focus on problem-solving ability, learning outcomes, engagement, and mathematical performance. Studies on Cognitive load tend to emphasize information processing, material complexity, thinking processes, and instructional strategies. The reviewed articles commonly use Cognitive load Theory, three dimensions of Cognitive load, questionnaires, and mathematical ability tests. Self-confidence has not been widely integrated with Cognitive load, although it may support students’ focus and mental effort in understanding mathematical concepts. This study concludes that the integration of Self-confidence and Cognitive load remains a research gap in mathematics learning. Abstrak Pembelajaran matematika menuntut keterpaduan aspek afektif dan kognitif, terutama ketika peserta didik menghadapi tugas yang kompleks. Penelitian ini bertujuan untuk menganalisis peran Self-confidence dalam Cognitive load pada pembelajaran matematika melalui pendekatan Systematic Literature Review. Kajian ini mengacu pada pedoman Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020. Data diperoleh dari Google Scholar dengan bantuan aplikasi Publish or Perish 8. Dari 100 artikel awal, sebanyak 17 artikel relevan dipilih untuk dianalisis. Hasil kajian menunjukkan bahwa penelitian Self-confidence lebih banyak berfokus pada kemampuan pemecahan masalah, hasil belajar, keterlibatan, dan performa matematis. Penelitian Cognitive load cenderung menekankan proses pengolahan informasi, kompleksitas materi, proses berpikir, dan strategi pembelajaran. Artikel yang dikaji umumnya menggunakan Cognitive load Theory, tiga dimensi Cognitive load, angket, dan tes kemampuan matematis. Self-confidence belum banyak diintegrasikan dengan Cognitive load, meskipun berpotensi mendukung fokus dan usaha mental peserta didik dalam memahami konsep matematika. Penelitian ini menyimpulkan bahwa integrasi Self-confidence dan Cognitive load masih menjadi celah kajian dalam pembelajaran matematika.